2019
DOI: 10.14232/rard.2018.1-2.92-97
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced biodegradability of dairy sludge by microwave assisted alkaline and acidic pre-treatments

Abstract: Considering the rapid, volumetric and selective heating effects of microwaves the microwave assisted chemical methods could provide appropriate alternatives for conventional thermal methods in sludge processing. Microwave irradiation alone is suitable to accelerate the hydrolysis stage of anaerobic decomposition of sludge resulted in accelerated biogas production rate and in higher biogas yield. Alkaline pre-treatments increase the organic matter solubility and suitable for disintegration of sludge particles. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Dogan and Sanin found that the SCOD/TCOD ratio could be increased by combining microwave irradiation with alkaline treatment up to 0.37, however, the level of pH plays a key role in the entire process, with pH 12.5 being the optimal one [43]. Beszédes et al also investigated the effects of different pH (ranging from pH 2-12) on the change in SCOD/TCOD ratio and found that at any given total irradiated microwave energy level (70 kJ/L, 150 kJ/L, 230 kJ/L) a pH of 12.0 resulted in the highest SCOD/TCOD ratio (0.33) [48]. Lemmer et al came to a similar conclusion; when combining microwave treatment with alkaline, increasing the alkaline dosage and microwave energy intensity, DD could be enhanced up to a certain point (about 50%) [49].…”
Section: Microwave-alkaline Combined Treatmentmentioning
confidence: 99%
“…Dogan and Sanin found that the SCOD/TCOD ratio could be increased by combining microwave irradiation with alkaline treatment up to 0.37, however, the level of pH plays a key role in the entire process, with pH 12.5 being the optimal one [43]. Beszédes et al also investigated the effects of different pH (ranging from pH 2-12) on the change in SCOD/TCOD ratio and found that at any given total irradiated microwave energy level (70 kJ/L, 150 kJ/L, 230 kJ/L) a pH of 12.0 resulted in the highest SCOD/TCOD ratio (0.33) [48]. Lemmer et al came to a similar conclusion; when combining microwave treatment with alkaline, increasing the alkaline dosage and microwave energy intensity, DD could be enhanced up to a certain point (about 50%) [49].…”
Section: Microwave-alkaline Combined Treatmentmentioning
confidence: 99%